The convergence properties of new hybrid conjugate gradient method - Mustafa, M.; Salih, Y.; Hamoda, M.A.; Sukono, . (2019)
In this paper, a new Hybrid Conjugate Gradient Methods is presented, which produced sufficient descent search direction at every iteration and global Convergence Properties for solving large-scale nonlinear optimization problem under exact line search. The numerical experiments show that a hybrid method has the best efficiency for the test problems.